Transcription factor Foxo1 is essential for IL-9 induction in T helper cells - Sakshi Malik (Nature Portfolio, 2017)
The transcription factor Foxo1 can control regulatory T cell and Th1 function. Here the authors show that Foxo1 is also critical for IL-9 production by Th9 cells and other IL-9-producing cells.